Вы находитесь на странице: 1из 7

Math 131A-3, Winter 2017

Midterm 1 on Wednesday, February 01, 2017

Name: . . . . . . . . . . . . . . . . . . . Student ID: . . . . . . . . . . . . . . . . . . .

Signature: . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .

Rules:

Duration of the exam: 50 minutes.

By writing your name and signature on this exam paper, you attest
that you are the person indicated and will adhere to the UCLA Student
Conduct Code.

No calculators, computers, cell phones (all the cell phones should be


turned off during the exam), notes, books or other outside material are
permitted on this exam. If you need more scartch paper, you should
ask for it from the supervisors. Do not use your own scratch paper!

Please, justify all your answers with mathematical precision and write
rigorous and clear proofs. You may loose points in the lack of justifi-
cation of your answers.

If using results proven in the book or lectures, state the theorem you
are using.

I wish you success!

Questions: 1 2 3 4 Total
Points: 25 25 25 25 100
Score:

1
Problem 1. Prove by induction that, if (xk )k0 is a sequence of integers
satisfying
x0 = 2 , x1 = 3 and xn = 3 xn1 2 xn2 for n 2 ,
then xn = 2n + 1 for all n 0 .

Solution. We have to prove by induction that, under the assumption


x0 = 2 , x1 = 3 and xn = 3 xn1 2 xn2 for n 2 ,
the following statement holds for all n N :
Pn : xk = 2k + 1 for every integer 0 k n .
That Pn is true for n = 1 , we can verify by direct computation:
x0 = 2 = 2 0 + 1 ,
x1 = 3 = 2 1 + 1 .
Now we assume that Pn is true for some n N and show that then Pn+1
is true. Thus we have to prove that if Pn is true, then
xn+1 = 2n+1 + 1 .
The proof: since
xn+1 = 3 xn 2 xn1
and, by Pn ,
xn1 = 2n1 + 1 and xn = 2n + 1 ,
we have
xn+1 = 3 (2n + 1) 2 (2n1 + 1) = 3 2n 2n + 1 = 3 2n 2n + 1
= 2n+1 + 1 .

u
t

2
Problem 2. Show that the set
n 2n 1 o
S := ;nN
3n + 4
is bounded above and compute sup S .

Solution by direct computation. b R is upper bound of S means that


the inequality
2n 1
b 2 n 1 3 b n + 4 b (3 b 2) n + 4 b + 1 0
3n + 4
holds for all n N . Since, for example, for b = 1 we have
(3 b 2) n + 4 b + 1 = (3 1 2) n + 4 1 + 1 = n + 5 > 0 for all n N ,
1 is an upper bound of S and consequently S is bounded above.
As we have seen above, the set of all upper bounds of S is

Sub := b R ; (3 b 2) n + 4 b + 1 0 for all n N .
Therefore the least upper bound sup S of S is the smallest element of Sub .
2
If the coefficient 3 b 2 of n vanishes, that is b = , then we have
3
2 11
(3 b 2) n + 4 b + 1 = 4 + 1 = > 0 for all n N ,
3 3
2 2
so Sub . But if b < 3 b 2 < 0 2 3 b > 0 , then
3 3
4b + 1
(3 b 2) n + 4 b + 1 < 0 for n > ,
2 3b
2
so b / Sub . Consequently is the smallest element of Sub , that is the least
3
upper bound sup S of S.

u
t

3
Solution by using knowledge on convergence of increasing sequences.
We notice that the elements of S are the elements of the sequence
2n 1 2 11 1
an := = , n 1.
3n + 4 3 3 3n + 4
1
Since the sequence , n 1 , is (strictly) decreasing, the sequence
3n + 4
(an )n1 follows to be (strictly) increasing.
Therefore, using the fact (discussed in class) that the least upper bound of
a bounded, increasing sequence of real numbers is the limit of the sequence,
we deduce :
1
2n 1 2
sup S = lim an = lim = lim n = 2.
n n 3 n + 4 n 4 3
3+
n
u
t

4
Problem 3. Let the set S R be bounded and containing at least two
elements. Prove that the set
{x R ; y1 < x < y2 for some y1 and y2 in S}

is equal to the open interval inf S, sup S .

Solution. Let a be the greatest lower bound of S, and b its least upper
bound.
Since, for every x Se := {x R ; y1 < x < y2 for some y1 and y2 in S},
we have a y1 < x < y2 b for appropriate y1 , y2 S, a is a lower bound
for S,
e and b is an upper bound for S. e Consequently, Se is bounded and
Se [ a , b ] = [ inf S , sup S ] .
Next we show that inf S and sup S dont belong to S,
e hence

Se inf S , sup S .
Assuming that sup S S, e there are y1 , y2 S such that y1 < sup S < y2 .
But this is not possible, because the (least) upper bound sup S of S can not
be strictly less than the element y2 of S.
Similarly follows that also inf S / S.
e
It remains to verify the inverse inclusion

inf S , sup S Se .

For let x inf S , sup S be arbitrary. Since x < sup S, x is no upper
bound of S, hence there exists some y2 S satisfying y2  x x < y2 .
Similarly, since x > inf S, x is no lower bound of S, hence there exists some
y1 S satisfying inf S  y1 y1 < x . Thus y1 < x < y2 for appropriate
y1 , y2 S, that is x S.
e

u
t

5
Problem 4. Let the sequence (an )n1 of real numbers be defined recursively
by setting

a1 = 2 and an+1 = 2 + an for n 1
r

 q
actually this means that an = 2 + 2 + ... + 2 . Show that (an )n1
| {z }
n square roots
is increasing and converges to 2 .

Solution. We verify by induction on n that the sequence (an )n1 is (strictly)


increasing: an < an+1 for all n N .
p
Since a2 = 2 + a1 = 2 + 2 > 2 + 0 = 2 = 11 , we have a1 < a2 .
Let us now assume that an < an+1 for some n N , and prove that then
an+1 < an+2 . Indeed,

an < an+1 = 2 + an < 2 + an+1


p
= an+1 = 2 + an < 2 + an+1 = an+2 .

Now we verify, again by induction, that the sequence (an )n1 is bounded
above.
In order to can prove by induction that b R is an upper bound for the
sequence (an )n1 , we must have

2 = a1 b

and an b should imply that 2 + an = an+1 b . Since

an b = 2 + an 2 + b ,

the implication an b = 2 + an b will follow once b satisfies

2 + b b.

So we have to choose some b 2 satisfying also

2 + b b 2 + b b2 b2 b 2 0 .
But, for b R ,
b2 b 2 0 b ( , 1 ] [ 2 , +) :

Since the roots of the equation b2 b 2 = 0 are



1 12 + 4 2 13 % 2
b1,2 = = ,
2 2 & 1

6
we have b2 b 2 = (b 2) (b + 1) . Therefore b2 b 2 0 means
that either
b 2 0 and b + 1 0 b 2 ,
or
b 2 0 and b + 1 0 b 1 ,
that is b ( , 1 ] [ 2 , +) .

Consequently the set of all b R satisfying b 2 and 2 + b b is
 
[ 2 , +) ( , 1 ] [ 2 , +) = [ 2 , +) .
Let us thus verify that, for example, 2 is an upper bound of (an )n1 :

Clearly, a1 = 2 < 2 .
On the other hand, if an 2 for some n N , then

an+1 = 2 + an 2 + 2 = 2 .
It follows by induction that an 2 for all n N .
Now, since (an )n1 is an increasing sequence
which is bounded above (by
2), it is convergent to a = sup an a1 = 2 > 0 . Passing to limits in
n1
(an+1 )2 = 2 + an ,
we deduce that a2 = 2 + a a2 a 2 = 0 . Thus a is one of the roots of
the equation a2 a 2 = 0 , that is (as we have already seen above) one of
the numbers

1 12 + 4 2 13 % 2
= .
2 2 & 1
Since a > 0 , we have
lim an = a = 2 .
n

u
t